Effects of drying as a preservation technique on nutrient contents of beef - Akhter, S; Rahman, M; Hossain, MM; Hashem, MA (Journal of the Bangladesh Agricultural University, 2010)
Effects of different drying methods (sun drying, oven drying & rural cooker smoking) and meat size (block, flat & mince) on the nutrient content of beef was investigated with cooked cured (CC) or non-cooked cured (NC) beef. Both physical and chemical assessment were done to assess the quality of meat. Organoleptically all the samples were in acceptable condition upto 120 days of storage time. The initial (30 days) DM, CP, EE and ash content, of the samples (g/100 g DM) were ranged from 81.32-90.00, 69.00-80.16, 2.90-5.23 and 15.00-18.01, respectively. The DM, CP and EE decreased and ash content increased with increasing storage time. At the end of 120 days of storage the DM, CP, EE and ash content of the samples (g/100 g DM) ranged from 79.00-87.36, 67.24-77.92, 1.90 - 4.00 and 19.00 - 24.70, respectively. DM and CP content in cooked meat was higher than non-cooked meat. However, cooked meat contains less EE and ash value than non-cooked meat. At the end of storing time rural smoked cooked block contain highest protein (77.92%) and oven dried non-cooked mince meat (67.24%) contain lowest protein percent. Statistical analysis revealed that there was a significant (P<0.5 to 0.01) effect of drying methods and meat size on cooked or non-cooked meat. The nutrient contents of meat sample degraded significantly (P<0.05 to 0.01) with the elapse of storage time. The quality decreasing trend was lower in smoked, cooked, flat size meat sample. From this study it was observed that rural cooker smoking method of meat drying could be a useful technique of meat preservation. Keywords: Drying methods; Meat sizes; Beef preservation; Nutrient content DOI: 10.3329/jbau.v7i1.4800 J. Bangladesh Agril. Univ. 7(1): 63-68, 2009